(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article analyzes the specifics of specialist participation in the investigative examination, its procedural aspects, and practical significance. The article examines the tasks, functions, and role of the specialist during the examination. The rights and obligations of the specialist and issues of their improvement are also considered. Based on the obtained results, proposals for improving the participation of specialists in the examination have been developed.